ANALYSIS OF INVESTMENT IN THE DEVELOPMENT OF THE WATU ULO FISHERY PORT IN JEMBER DISTRICT REVIEWED FROM FINANCIAL ASPECTS AND SENSITIVITY ASPECTS - Ratuinsani, Tati Mushalihati; Haris Muhammadun; Laksono Djoko Nugroho (International Journal Science and Technology, 2024)
Watu Ulo Beach is a concentration of fishing communities as a place to fill supplies to catch fish at sea and as a landing place for fish catches. The local government intends to build a fishing port in Watu Ulo to improve facilities and infrastructure for fishermen in catching fish. This study aims to determine the feasibility of investment in the development of fishing ports in terms of financial aspects and sensitivity. The research method uses three scenarios for the value of income, namely the pessimistic scenario, moderate scenario, optimistic scenario. The results of the financial feasibility analysis using the NPV, IRR, BCR, and PP methods were declared feasible for the moderate scenario and optimistic scenario while the pessimistic scenario analysis results were not feasible because the IRR (6.15%) < MARR (7.72%) The results of the sensitivity analysis stated that with three scenarios on the Value of Revenue and Operating Costs obtained the results of Sensitivity The value of revenue for the pessimistic scenario is sensitive at -13.67% if it is smaller than that the investment becomes unfeasible. The revenue value for the moderate sensitive scenario is -39.96% if it is smaller than that the investment becomes unfeasible. The value of income for an optimistic scenario is sensitive at -40.75% if it is smaller than that, the investment becomes unfeasible. The revenue value for the optimistic scenario is sensitive at -40.75%, if it is smaller than that, the investment is not feasible. And if the Operating Cost Sensitivity for the pessimistic scenario is sensitive at -15.96%, if it is smaller than that, the investment is not feasible. Operating Costs for a moderate sensitive scenario at +22.67% if it is greater than that, the investment becomes unfeasible. Operating Costs for the optimistic scenario are sensitive at 25.59% if greater than that then the investment becomes unviable.